KARAKTERISTIK DEWAN KOMISARIS DAN IDIOSYNCRATIC VOLATILITY - Sansaloni Butar Butar (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
CAPM has been used as a widely accepted model forstock valuation. According to CAPM, stock risks comprise of systematic and unsystematic risks. The latter is also called idiosyncratic risk. Since idiosyncratic riskis induced by firm-specific factors, it can be removed by forming portfolio. However, some empirical findings in various capital markets indicate that idiosyncratic risk cannot be completely eliminated. Thus, stock price movements may also be influenced by firm-specific factors. Volatility of stock price movements induced by firm- specific information are commonly called idiosyncratic volatility. The objective of this research is to provide evidence of the association between Board of Commissioners characteristics and idiosyncratic volatility in Indonesian capital market. More specifically, the characteristics include Board of Commissioners independence, size, gender diversity, busyness, and meeting frequency. Using sample of indonesian public firms in 2013-2017, regression analysis show that Board size and meeting frequency are inversely related with idiosyncratic volatility. However, Board independence, gender diversity, and busyness have no effect on idiosyncratic volatility. The practical implication of this study is that firms should establish Board of Commissioners with larger membership and urge Board of Commissioners to conduct more frequent meeting to discuss financial reporting-related issues.